Ancaman dan Pencegahan Phishing Pengguna Media Sosial untuk Siswa di SMK Wisata Indonesia - Andri Andri; Somawati Somawati (Jurnal Kemitraan Masyarakat, 2025)
In these modern days, it is very difficult to find a person who is far from the internet or from their smartphone devices. The phenomenon that arises is that almost everyone now has more than one social media account. Social media itself, besides functioning as a space for socializing, is also used as a business platform, like online stores, due to the increasing number of users. However, when this opportunity exists, cybercriminals also prowl in search of easy ways to profit from unsuspecting users. One of the methods they rely on is phishing techniques. Phishing is a scenario designed to deceive people into unknowingly handing over their personal data to the trapper. By providing education about threats and ways to prevent this type of attack on social networking platforms, it is hoped that the public can become more critical and suspicious of suspicious signs on accounts or other web pages, as well as take appropriate preventive measures.